2014
DOI: 10.5433/1679-0359.2014v35n3p1463
|View full text |Cite
|
Sign up to set email alerts
|

Macro ingredientes como indicadores da qualidade de mistura de rações

Abstract: ResumoFoi conduzido um trabalho para avaliar o uso de macro ingredientes como indicadores da qualidade de mistura de rações. Foram utilizados (como marcadores): milho pipoca, sorgo, milheto, arroz colorido, milho roxo moído (adicionados em 0,5% na ração, em substituição ao milho moído) e o calcário grosso peneirado em peneira ABNT nº10 com dois milímetros de diâmetro das malhas (adicionado em 0,5% na ração, em substituição ao calcário finamente moído). Como método referência utilizouse microtracer F-Red. Foi u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
3
0
1
Order By: Relevance
“…The increase in grinding intensity obtained by reducing the screen hole diameter (screen used to surround the grinding chamber in hammer mill) makes it difficult for the corn to leave the crushing chamber in the grain process, with a consequent greater number of hammer impacts on the corn particles, which leads to reduced PS and GSD (Table 2). This reduction in GSD with the reduction in PS is a relatively common behavior and has already been reported by Paiano et al (2014); Rojas and Stein (2015); Chiodelli, Folador, Boiago, Carvalho, and Paiano (2018) and Gebhardt et al (2018); said behavior is associated with grain reprocessing, which is characterized by reduced particle size variability.…”
Section: Feed and Diets Characteristicssupporting
confidence: 60%
See 1 more Smart Citation
“…The increase in grinding intensity obtained by reducing the screen hole diameter (screen used to surround the grinding chamber in hammer mill) makes it difficult for the corn to leave the crushing chamber in the grain process, with a consequent greater number of hammer impacts on the corn particles, which leads to reduced PS and GSD (Table 2). This reduction in GSD with the reduction in PS is a relatively common behavior and has already been reported by Paiano et al (2014); Rojas and Stein (2015); Chiodelli, Folador, Boiago, Carvalho, and Paiano (2018) and Gebhardt et al (2018); said behavior is associated with grain reprocessing, which is characterized by reduced particle size variability.…”
Section: Feed and Diets Characteristicssupporting
confidence: 60%
“…Particle size is one of the physical factors with the greatest impact on swine nutrition, since most of the digestion is carried out through endogenous enzymes (Vukmirovic et al, 2017). Reducing particle size improves feed efficiency and increases animal performance due to better nutritional digestibility (Al-Rabadi et al, 2017;Bao et al, 2016;Rojas & Stein, 2015), in addition to interfering with the quality of feed mixtures (Paiano et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This fall can result in particles being separated, which is a process influenced by difference in the specific weight that is due to the characteristics of the rWA material. Paiano et al (2014) reported that ingredients with excessively different physical characteristics can segregate and promote desmixing of the feed, which may explain the results obtained during this study. In a study performed by Scheideler (1995) for evaluate pellets quality, the percentages of thick in the feed mill pellet cooler, transportation through feed truck and feeding troughs, can deteriorate and induce the end of process, reach 66.6, 48 and 41.5 %, low values than those found in our study (77.49, 73.12 and 45.05 %) at the same collection stages, respectively.…”
Section: Resultsmentioning
confidence: 51%
“…Despite them, most of the productive expenses of the activity have been related to animal feeding, representing more than 60-70 % of its total cost. According to Paiano et al (2014), the maximum nutritional utiliza-tion of food depends on numerous factors involved on feed production, especially the mixture.…”
Section: Introductionmentioning
confidence: 99%
“…O maior desgaste dos marteletes resultou em aumento linear (P<0,05) para DGM e DPG do milho moído, resultados associados às arestas arredondadas dos marteletes desgastados, os quais proporcionaram menor eficiência na moagem o que aumentou o DGM, o reprocessamento do grão e por consequência aumentou o DPG. Resultados parecidos foram obtidos por Paiano et al (2014) e Rojas e Stein (2015) os quais relataram aumento no DPG com o aumento do DGM da moagem do milho.…”
Section: Características Operacionaisunclassified